Premature Ejaculation: Do We Need to Address the Issue Differently?. Issue 2 (April 2019) - M., Shivalingaiah; S., Anuradha; Bhat, Gajanan S.
Abstract: Introduction: Premature ejaculation is a complex condition with controversial management modalities. We decided to assess the treatment-seeking behavior of affected couples, which is an indirect indicator of the efficacy of the present management modalities of premature ejaculation. Materials and Methods: Couples, who reported premature ejaculation at our outpatient clinics between January 2015 and December 2016, were enrolled in the study. Patients with acquired causes for premature ejaculation were excluded. Both the partners were administered premature ejaculation diagnostic tool (PEDT) questionnaire separately at the time of initiation of the study and after 1 month. They were asked to report intravaginal ejaculatory latency time (IELT) and their treatment-seeking behavior at these time intervals. The couples were counselled regarding their diagnosis and offered treatment with dapoxetine 30 mg as and when required. Results: A total of 117 couples with an average married life of 5.4 years were enrolled for the study. Among these, 68 had premature ejaculation (PE), 30 had probable PE and 19 had no PE as estimated on PEDT. Post treatment, 55% of couples with PE, 47% of couples with probable PE and 55% of couples without PE wanted to continue treatment seeking despite improvement. Female partners had the desire to seek treatment despite the male partner reporting otherwise. Conclusion: The treatment seeking behavior of the affected couple indicates the inefficacy of the present management modalities of PE. As specialized health care providers, we need to address these concerns to provide a comprehensive solution to their problems.